2022
DOI: 10.1155/2022/6360133
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 Prevents Glucocorticoid-Induced Osteonecrosis of the Femoral Head in Rats

Abstract: Objective. Glucocorticoid-induced osteonecrosis of the femoral head is one of the most common causes of nontraumatic osteonecrosis of the femoral head, but its exact pathogenesis remains unclear. The aim of this study was to investigate the role of SIRT6 in the maintenance of bone tissue morphology and structure, intravascular lipid metabolism, and its potential molecular mechanism in glucocorticoid-induced osteonecrosis of the femoral head. Methods. SIRT6 adenovirus was transfected into GIONFH in rats. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Melatonin has been shown to regulate SIRT6, thereby inhibiting ferroptosis and delaying age-related cataract [ 33 ]. SIRT6 has been reported to prevent osteonecrosis of the femoral head by inhibiting ferroptosis [ 15 ]. In the present study, the inhibition of SIRT6 was found to enhance LPS-induced ferroptosis in ALI, thereby indicating that ferroptosis is an essential factor involved in the SIRT6-mediated protection against ALI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin has been shown to regulate SIRT6, thereby inhibiting ferroptosis and delaying age-related cataract [ 33 ]. SIRT6 has been reported to prevent osteonecrosis of the femoral head by inhibiting ferroptosis [ 15 ]. In the present study, the inhibition of SIRT6 was found to enhance LPS-induced ferroptosis in ALI, thereby indicating that ferroptosis is an essential factor involved in the SIRT6-mediated protection against ALI.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 has been shown to exert protective effects in various diseases [ 13 , 14 ]; however, the role of SIRT6 in ALI remains unclear. Recent studies have demonstrated that SIRT6 exerts its biological effects by regulating p53-mediated ferroptosis [ 15 , 16 ]. In the present study, we investigate the protective effect of SIRT6 against LPS-induced ALI by the regulation of p53-mediated ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SIRT6 has been demonstrated to inhibit nuclear transcription of NF-κB and inactivate NF-κB to facilitate ferroptosis in pancreatic cancer, thereby exerting anti-tumor effects ( Gong et al, 2022 ). Fang et al (2022) demonstrated that SIRT6 overexpression could reverse the decreased levels of GPX4, SLC7A11, and GSH and reduce the cellular accumulation of MDA and ROS to inhibit ferroptosis, ultimately restoring bone formation and angiogenesis and relieving femoral head necrosis. Mi et al demonstrated that melatonin inhibited ferroptosis in rat lens epithelial cells through SIRT6/p-NRF2/GPX4 and SIRT6/NCOA4/FTH1 pathways, neutralized lipid peroxidation toxicity, and delayed the formation of cataract caused by ultraviolet rays exposure ( Mi et al, 2023 ).…”
Section: Roles Of Sirtuins In Ferroptosismentioning
confidence: 99%
“…Recently, an experimental study observed a decreased expression of GPx4 protein in the femoral head of rat model of osteonecrosis. [ 7 ] This highlights the crucial role of GPx4 in the pathogenesis of NONFH.…”
Section: Introductionmentioning
confidence: 95%